Dynamic friction and the seismic performance of geosynthetic interfaces. Issue 6 (December 2018) - Pavanello, P.; Carrubba, P.; Moraci, N.
Abstract: The stability of geotechnical structures which contain geosynthetic interfaces is closely linked to the shear strength between the geosynthetics themselves, both in static and dynamic conditions. Static friction is the maximum interface shear strength mobilised before displacement, whereas dynamic friction is related to the kinematics of the displacement itself. In polymer materials, dynamic friction may be widely variable, depending on the type, geometry and integrity of the surfaces in contact, as well as on the intensity and time-history of the seismic signal. This means that predicting interface shear strength is not simple. This paper focuses on the evaluation of dynamic interface shear strength between geosynthetics, using the results of both inclined plane tests and shaking table tests; this latter test also provided a means to analyse interface behaviour under the conditions of real seismic records. To this purpose, two common geosynthetic interfaces, which exhibit different behaviour under dynamic loading, were tested. One interface was a smooth HDPE geomembrane in contact with a nonwoven polypropylene geotextile, while the second was a textured HDPE geomembrane in contact with a different type of nonwoven polypropylene geotextile. The test results shows that dynamic friction mobilised during seismic events depends on the relative speed according to the same law outlined by the free sliding tests and by the shaking table tests carried out with sinusoidal base motions. Moreover, for the two different types of studied interfaces dynamic friction may be greater, lesser or equal to the static friction and the assumption of a constant value of dynamic friction does not lead to an accurate prediction of the seismic displacements under various earthquakes.